Pengaruh Keakraban Guru Dan Peserta Didik Islam-Kristen Terhadap Motivasi Belajar Dan Minat Belajar Di Sma Negeri 13 Ambon - Bakri - (Peneliti.net, 2019)
This study aims at 1) to describe the intimacy of teachers and Islamic-Christian students in Ambon State High School 13, 2) to describe the learning motivation of Islamic-Christian students in SMA Negeri 13 Ambon 3) to describe the learning interests of Islamic-Christian students in high school Negeri 13 Ambon 4) To analyze the influence of teacher familiarity with Islamic-Christian students on students 'learning motivation in SMA Negeri 13 Ambon 5) To analyze the influence of teacher familiarity with Islamic-Christian students on students' learning motivation in Public High School 13. The research approach used is quantitative descriptive with a total sample of 93 people by collecting data from respondents using questionnaires while the data analysis technique uses simple linear regression and T test. The results of the study show that 1) there is teacher familiarity with Islamic-Christian students; 2) there is motivation to learn as well; 3) there is also interest in learning at Ambon State High School 13. Of the three variables can be categorized well. The results of the analysis ofteacher and Islamic-Christian students have an influence with the known significant value of 0,000 <from the probability value of 0.005 or also with the value of tcount 2.044> ttable of 1.986 at a significant 0.025; while keakraban teachers and learners of Islamic-Christian influence with simple linear regression test with a known value of the significant value of 0.000 <of a probability value of 0.005 or also withtvaluethe 3,095 > ttable of 1.986 at significant 0.025. This shows the familiarity of teachers and students categorized well and there is an influence of the familiarity of teachers and students towards learning motivation and interest in learning.